2021
DOI: 10.1002/hed.26944
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive gene cluster analysis of head and neck squamous cell carcinoma TCGA RNA‐seq data defines B cell immunity‐related genes as a robust survival predictor

Abstract: Background The authors aimed to define novel gene expression signatures that are associated with patients' survival with head and neck squamous cell carcinoma (HNSCC). Methods TCGA RNA‐seq data were used for gene expression clusters extraction from 499 tumor samples by the “EPIG” method. Tumor samples were then partitioned into lower and higher than median level groups for survival relevant analysis by Kaplan–Meier estimator. Results We found that two gene clusters (_1, _2) are favorably, while two (_3, _4) ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 67 publications
0
9
0
Order By: Relevance
“…JCHAIN is also a new B-cell prognostic biomarker that can predict OS in HNSCC [32,33]. Many studies have shown a relationship between B-cell immunity and a good prognosis for patients with HNSCC [32][33][34]. We found that JCHAIN was a highly expressed protective gene in the low-risk group.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…JCHAIN is also a new B-cell prognostic biomarker that can predict OS in HNSCC [32,33]. Many studies have shown a relationship between B-cell immunity and a good prognosis for patients with HNSCC [32][33][34]. We found that JCHAIN was a highly expressed protective gene in the low-risk group.…”
Section: Discussionmentioning
confidence: 58%
“…JCHAIN (also known as IGJ) encodes the immunoglobulin J chain, the unit that connects IgA and IgM monomers, and it has decreased expression in HNSCC and is related to a better prognosis [31]. JCHAIN is also a new B-cell prognostic biomarker that can predict OS in HNSCC [32,33]. Many studies have shown a relationship between B-cell immunity and a good prognosis for patients with HNSCC [32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…An association between J chain expression and an increased OS has been observed in other tumor types, supporting our observation. Xin Feng et al identified a gene signature that includes the J chain gene able to discriminate head and neck squamous cell carcinoma patients with better overall survival probability [ 68 ]. Moreover, recent studies revealed that a high J chain expression is associated with better prognosis in sarcoma [ 69 ] and breast cancer patients [ 70 , 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Y-linked genes favorable to overall survival were extracted by a previously reported method, "extracting gene expression patterns and identifying co-expressed genes" (EPIG). 15,26 EPIG is an unsupervised cluster extraction method that goes through a pair-wised correlation evaluation among all the genes to extract all the possible clusters with a given correlation threshold. The genes in each of the extracted patterns are highly similar in their expression profiles, which may be caused by coexpression to underlying biological cause.…”
Section: Methodsmentioning
confidence: 99%
“…14 We have recently identified several clusters of coexpressed genes that are associated with HNSCC overall survival by 1 Departments of Otolaryngology, Wake Forest School of Medicine, Winston-Salem, North Carolina, USA analyzing TCGA dataset. 15 Briefly, 4 clusters of coexpressed genes were identified, with 2 of them favorable and 2 of them unfavorable to HNSCC overall survival. In addition, their association with survival is independent of other clinical condition, for instance, HPV status or tumor sites.…”
mentioning
confidence: 99%